Catalytic applications of magnetic nanoparticles functionalized using iridium N-heterocyclic carbene complexes1. (27th August 2015) - Iglesias, Diego; Sabater, Sara; Azua, Arturo; Mata, Jose A.
<x xml:space="preserve">Abstract</x> The development of a synthetic modular methodology for the preparation of catalytic materials based on magnetic nanoparticles with iridium complexes and their application to transfer hydrogenation.